Precision technological indices for nutrition and plant protection technology for strawberries grown in the open field - F.C Marin; E. Chiţu; M. Călinescu; M. Sumedrea; M. Sturzeanu; M. Militaru; I. Viscol; M. Coman (Romanian Journal of Horticulture, 2021)
This paper presents the efforts carried out at Research Institute for Fruit Growing between 2020-2021, in order to assess the strawberry behaviour to the hydric and biocenotic stress to improve the water and nutrients use and to build precision driven technologies that can be transferred to the farmers. Thirteen strawberry cultivars and three promising hybrids were evaluated in the field in order to evaluate the response to the fertirrigation regime, the chlorophyll fluorescence and the photosynthetic potential. We also focus on the behavior of the cultivars to the major pest and diseases, forecasts using warning modules, and an innovative mobile application and warning algorithms elaborated on the computer, and productivity potential into the first year of fructification. The ratio between the main macro-elements N 12.5: P 18.0: K 1.0: Mg 1.5 aiming to provid a very good nutrition to the strawberry plants and preparation for the cold season. The varietal sensitivity index to diseases (VSI%) of the newly introduced cultivars, ranged between 0.48 at 'Dona' cultivar and 2.53 at 'Mira' cultivar but no more than 5.00 at 'Elsanta' cultivar. The average fruit weight ranged between 18.5 g at 'Daroyal' and 27.5 at 'Alba' cultivars. So, in this group, the productivity potential ranged between 451 to 1100 g /plant.